1996
DOI: 10.1002/(sici)1097-4644(19961201)63:3<280::aid-jcb3>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

PML-containing nuclear bodies: Their spatial distribution in relation to other nuclear components

Abstract: PML-containing nuclear bodies: their spatial distribution in relation to other nuclear components Grande, M.A.; van der Kraan, K.; van Steensel, B.; Schul, W.; de The, H.; van der Voort, H.T.M.; de Jong, L.; van Driel, R. Link to publicationCitation for published version (APA): Grande, M. A., van der Kraan, K., van Steensel, B., Schul, W., de The, H., van der Voort, H. T. M., ... van Driel, R. (1996). PML-containing nuclear bodies: their spatial distribution in relation to other nuclear components. Journal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
2

Year Published

1998
1998
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 49 publications
(46 reference statements)
9
101
2
Order By: Relevance
“…However, PML nuclear bodies do not associate with sites of active transcription and do not localize with nascent DNA (Melnick and Licht, 1999). General transcription factors like TFIIH and RNA Polymerase II do not co-localize with PML bodies (Grande et al, 1996). Consistent with these ®ndings, we observe no association between PML and RNA polymerase II (Figure 2a).…”
Section: Discussionsupporting
confidence: 87%
“…However, PML nuclear bodies do not associate with sites of active transcription and do not localize with nascent DNA (Melnick and Licht, 1999). General transcription factors like TFIIH and RNA Polymerase II do not co-localize with PML bodies (Grande et al, 1996). Consistent with these ®ndings, we observe no association between PML and RNA polymerase II (Figure 2a).…”
Section: Discussionsupporting
confidence: 87%
“…The staining presented a punctuate distribution throughout the nuclei except for the nucleoli and the perinuclear chromatin, which remained unlabelled. This pattern of labeling is specific for proteins implicated in the transcriptional process (Grande et al, 1997). For CD11/HPAF cells, a mild reactivity was detected in the nuclei.…”
Section: C C T T C C a G A T G A G G 14 551mentioning
confidence: 79%
“…ND10s have been proposed to act as nuclear sensors that can detect exogenously introduced proteins (6,44). It has been demonstrated that ND10s assemble at precise subnuclear locations frequently adjacent to compartments that participate in RNA processing, including Cajal bodies, cleavage bodies, and SC35-positive splicing sites (45,46). This proximity suggests that ND10 could also play a part in such events.…”
Section: Discussionmentioning
confidence: 99%